3M DISCIPLINE COUNSELING (USING MASKS CORRECTLY, WASHING HANDS WITH SOAP, KEEPING DISTANCE) IN THE NEW NORMAL ERA COVID-19 - Ida Herwati (Indonesian Journal of Health Care Management, 2020)
Early in 2020, the world was shocked by the spread of new viruses, namely the new type of corona virus (SARS-CoV-2) and the disease Corona virus disease 2019 (Covid - 19). The spread of COVID-19 occurs rapidly and is widespread because it can be transmitted through human-to-human contact human. Indonesia has implemented various public health measures including Large-Scale Social Restrictions (PSBB), in the Context of Prevention and Handling of Corona Virus Disease 2019 (COVID-19) such as 3M Discipline (Wearing Masks Correctly, Washing Hands with Soap, Maintaining Distance). The purpose of this activity is to increase knowledge and understanding of covid-19 prevention. The method used in this activity is online using the Zoom application on October 29, 2020 using the lecture method. The lecture method was chosen to provide an explanation of 3M discipline and how to wear masks properly, how to wash hands 6 steps. The question and answer method is also implemented so that participants can gain as much knowledge as possible about the material presented. Through this activity, it is hoped that the public can realize that the prevention of Covid-19 is very important, one of which is by getting used to using masks properly, washing hands with soap and maintaining distance. The results of the activity showed a significant increase in the knowledge and ability of the participants to understand the material presented. Theresults post-test showed an increase in the percentage of up to 100% for questions related to knowledge about Covid-19 prevention and 3M discipline (wearing masks properly, washing hands with soap, keeping distance).